A Study of Child Feeding Practices of Mothers and Their Association with Nutritional Status of Child in an Urban Slum Area of Solapur - Rajput, Rupali R; Santosh, Jagannath H; K. M Suresh (National Journal of Community Medicine, 2018)
Background: Countrywide data from NFHS-lll (2005-2006) documented that only 57% women practiced prelacteal feeding, proportion of exclusively breastfed infants at 6 months of age was 46.4%. The study was conducted to know breast feeding practices; to know nutritional status of child and to study the association between breast feeding practices and nutritional status of child. Methods: The study was community based descriptive study with cross sectional design. A mother of infant and infant of age 6-12 months from the study area were the sampling unit. Sample size was calculated to be 400 considering 46.4% exclusively breast feeding rate in India according to NFHS-3. Results: Out of 400, 37% mothers initiated breastfeeding within 1-4 hour of delivery, 41.25% mothers practice exclusive breast feeding, 90.5% mothers fed colostrum to their babies, 26.75% mothers gave prelacteal feed to their babies. Prevalence of stunting, underweight, overweight, obesity was 38.25%, 32.25%, 3.75%, 2% and wasting was 20%. Conclusion: Breastfeeding practices like exclusive breast feeding; prelacteal feeding was less than the national average in present urban slum. Child feeding practices had direct association with nutritional status of child in present study.